A novel color image encryption algorithm based on fractional-order conservative memristive hyperchaotic system and extended zig-zag transform - Fanqi Meng; Gang Wu; Juxiao Zhang (Journal of King Saud University: Computer and Information Sciences)
Abstract Color images are a valuable information carrier. This paper presents a novel image encryption scheme based on fractional-order conservative memristive hyperchaotic system (FCMHS) and extended Zig-Zag transform to protect images from being attacked. First, the dynamic characteristics of FCMHS were systematically studied and analyzed, and its potential application value in the field of information security is verified. The pseudo-random sequences generated by FCMHS passed all the tests of the National Institute of Standards and Technology (NIST). Second, a new extended Zig-Zag confusing method is designed, which realizes the scrambling of pixels in different channels of a color image. Finally, the performance of the designed encryption algorithm is analyzed using key space, information entropy, histogram, differential attack, correlation coefficient and robustness analysis. The average number of pixels change rate (NPCR) and uniform average change intensity (UACI) values of the encryption scheme are 99.61% and 33.46%, respectively. Additionally, the encryption time is only 0.12533 s for a color image of size $$256× 256$$ 256 × 256 . The experimental results demonstrate that our algorithm has better encryption performance and security.